Studia i praca – jakie są skutki dla poziomu aktywności fizycznej studentów? = How College and employment affects the level of physical activity of students? - Dudło, Aleksandra; Duda, Mariola; Knapik, Andrzej (Journal of Education, Health and Sport, 2016)
Dudło Aleksandra, Duda Mariola, Knapik Andrzej. Studia i praca – jakie są skutki dla poziomu aktywności fizycznej studentów? = How College and employment affects the level of physical activity of students? Journal of Education, Health and Sport. 2016;6(7):138-146. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57296 http://ojs.ukw.edu.pl/index.php/johs/article/view/3667 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Studia i praca – jakie są skutki dla poziomu aktywności fizycznej studentów? How College and employment affects the level of physical activity of students? Aleksandra Dudło1, Mariola Duda1, Andrzej Knapik2 1Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach, STN przy Zakładzie Adaptowanej Aktywności Fizycznej i Sportu 2Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach Streszczenie Celem badania było określenie związków między podejmowaniem pracy zawodowej a poziomem aktywności fizycznej wśród studentów uczelni wyższych. Zbadano 245 osób za pomocą autorskiej ankiety oraz kwestionariusza aktywności fizycznej SEWL. Analiza statystyczna polegała na wykonaniu statystyk opisowych. Porównań dokonano za pomocą analizy wariancji ANOVA. Kobiety częściej podejmują pracę zawodową podczas studiów. Przeważająca część studentów deklaruje podejmowanie aktywności fizycznej, jednakże mężczyźni częściej zajmowali się sportem na profesjonalnym poziomie. Słowa kluczowe: aktywność fizyczna, praca, studia. Abstract The aim of the study was to determine the relationship between the taking of work and the level of physical activity among college students. 245 students were tested using an original questionnaire and SEWL questionnaire. The analysis consisted of descriptive statistics and performed analysis ANOVA. Women are more likely to work during study. The majority of students declare physical activity, but men often participate in the sport at a professional level. Keywords: physical activity, work, study.